2017
DOI: 10.3389/fpsyg.2017.00982
|View full text |Cite
|
Sign up to set email alerts
|

Security under Uncertainty: Adaptive Attackers Are More Challenging to Human Defenders than Random Attackers

Abstract: Game Theory is a common approach used to understand attacker and defender motives, strategies, and allocation of limited security resources. For example, many defense algorithms are based on game-theoretic solutions that conclude that randomization of defense actions assures unpredictability, creating difficulties for a human attacker. However, many game-theoretic solutions often rely on idealized assumptions of decision making that underplay the role of human cognition and information uncertainty. The consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…A useful framework for studying decision‐making under deception is with economic signaling games (Jenkins, Zhu, & Hsu, 2016; Moisan & Gonzalez, 2017). Signaling games are two‐player games involving a sender and a receiver with incomplete information (Pawlick, Colbert, & Zhu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A useful framework for studying decision‐making under deception is with economic signaling games (Jenkins, Zhu, & Hsu, 2016; Moisan & Gonzalez, 2017). Signaling games are two‐player games involving a sender and a receiver with incomplete information (Pawlick, Colbert, & Zhu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is because a random agent was less likely to turn back to the original location given a nonvisible swap event, and the IBL observer "thought" that the random agent saw the swap event. This is an interesting and unexpected result given situations in which random agents could be used to deceive humans (Moisan & Gonzalez, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Moisan and Gonzalez found that game theoretical algorithms miss out on advantages provided by knowledge of the threat actorsâĂŹ cognition [21]. These game theoretical solutions assume an idealized decision making on the part of the threat actors, and therefore have limited adaptability against them.…”
Section: Customized Deceptionmentioning
confidence: 99%